Risk Factors for Stunting Incidence in Children Under Three in the Working Area of the Korbafo Community Health Center, Pantai Baru Sub-District, East Nusa Tenggara - Aprianjen Yehentina Kekado; Lewi Jutomo; Rut Rosina Riwu (Journal of Health Promotion and Behavior, 2024)
Background: The incidence of stunting in children under three can be generated by several factors, namely family income, maternal education, maternal knowledge concerning nutrition, energy intake, and protein intake. This study aimed to discover the risk factors for stunting in children under three in Korbafo Community Health Center working area, Pantai Baru Sub-District in 2022. Subjects and Method: The analytical survey study with a case-control study design was conducted in Korbafo Community Health Center working area, Pantai Baru Sub-District, East Nusa Tenggara. A total of 96 children under three divided into 2 groups, 48 children in case group and the other 48 in control group, were selected using purposive sampling. The dependent variable was the incidence of stunting. The independent variables consisted of family income, maternal education, maternal knowledge concerning nutrition, energy intake, and protein intake. The data were analyzed using a simple logistic regression test. Results: The incidence of stunting in children under three increased with low family income (b = 1.29; 95% CI= 1.46 to 9.20; p= 0.006), low maternal education (b= 1.69; 95% CI= 2.26 to 13.20; p< 0.001), insufficient maternal knowledge concerning nutrition (b = 2.19; 95% CI= 3.57 to 22.67; p< 0.001), inadequate energy intake (b= 1.86; 95% CI= 2.48 to 16.61; p< 0.001),  and inadequate protein intake (b= 1.79; 95% CI= 2.47 to 14.56; p< 0.001), and they were statistically significant. Conclusion: The incidence of stunting in children under three years increases with low family income, low maternal education, insufficient maternal knowledge concerning nutrition, inadequate energy intake, and inadequate protein intake.